Method for detecting element content of lithium aluminum titanium phosphate solid electrolyte

By mixing lithium titanium aluminum phosphate with a specific proportion of mixed acid solution and performing low-temperature heating and digestion, the problem of difficulty in dissolving lithium titanium aluminum phosphate is solved, and accurate quantitative analysis of its elemental content is achieved.

CN119290552APending Publication Date: 2025-01-10ZHEJIANG AIKE NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411283938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively dissolve lithium titanium aluminum phosphate, thereby conducting quantitative analysis of its elemental composition.

Method used

By mixing lithium titanium aluminum phosphate with a specific proportion of mixed acid solution (a mixture of nitric acid, hydrochloric acid and hydrofluoric acid), and performing low-temperature heating and digestion, a solution that can be used for ICP-OES detection is obtained.

Benefits of technology

It achieves the complete dissolution of lithium titanium aluminum phosphate, accurately detects its element content, and solves the problem of quantitative analysis. The process is simple and highly accurate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290552A_ABST
    Figure CN119290552A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a method for detecting the element content of a lithium aluminum titanium phosphate solid electrolyte. The detection method comprises the following steps: firstly, preparing mixed acid, and digesting the solid electrolyte by adopting a conventional method to obtain a clear and transparent solution; secondly, the solution is divided into two parts after being diluted to a constant volume, one part is diluted to a certain proportion and then used for testing the content of main elements including lithium, aluminum, titanium and phosphorus in the solid electrolyte, and the other part is used for testing the content of impurity elements in the solid electrolyte; finally, standard solutions of lithium, aluminum, titanium and phosphorus elements and standard solutions of impurity elements are prepared respectively, and the content of main elements and the content of the impurity elements in the solid-state electrolyte lithium aluminum titanium phosphate are measured through ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometer). By adopting the detection method disclosed by the invention, the lithium titanium aluminum phosphate solid electrolyte can be quickly and completely digested, the contents of main elements and impurity elements of the lithium titanium aluminum phosphate solid electrolyte can be accurately determined, the test method is simple, the result is accurate, the repeatability is good, and the problem of component detection of the lithium titanium aluminum phosphate of the solid electrolyte is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte. Background Art

[0002] As one of the mainstream technologies of power batteries today, lithium-ion batteries have attracted much attention due to their advantages such as high energy density, low operating voltage, safety and reliability. Traditional lithium-ion batteries use electrolytes containing flammable organic solvents, which pose safety hazards such as flammability, explosion and leakage. Solid electrolytes have high ionic conductivity, wide electrochemical window, good chemical stability and high mechanical strength, which can effectively inhibit the growth of lithium dendrites and prevent short circuits in batteries. The development of all-solid-state lithium-ion batteries based on solid electrolytes is expected to solve the safety problems of lithium batteries.

[0003] Among the many solid electrolytes, NASICON-type lithium aluminum titanium phosphate Li 1+x Al x Ti 2-x (PO4)3(0<x<2) solid electrolyte material has high ionic conductivity (room temperature ionic conductivity>10 -4 S / cm), low cost and air stability, making it the solid electrolyte closest to commercialization. NASICON-type structural materials have an open framework with fast ion diffusion capabilities, which allows them to embed and migrate alkali metal ions or alkaline earth metal ions without major structural changes, causing structural collapse and thus affecting cycle life. Titanium-based phosphate framework structural materials have the advantages of high structural stability, easy production and rich structural diversity, making them ideal solid electrolyte materials.

[0004] Inductively coupled plasma optical emission spectroscopy (ICP-OES) is an effective means of quantitative elemental analysis. It requires that the sample to be analyzed be completely dissolved in order to accurately characterize its components. The structure of lithium aluminum titanium phosphate is extremely stable, making it difficult to quantitatively analyze its elemental composition. Currently, there is no effective method to completely dissolve lithium aluminum titanium phosphate. Finding an effective means to completely digest lithium aluminum titanium phosphate so that ICP-OES can be used to accurately characterize its components is of great practical significance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to solve the problem that there is currently no effective method to dissolve lithium aluminum titanium phosphate so as to quantitatively characterize it, and a method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte is provided.

[0006] The present invention provides a method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte, comprising the following steps:

[0007] S1: mixing lithium aluminum titanium phosphate solid electrolyte powder to be tested with a mixed acid solution to obtain a mixed solution, wherein the mixed acid solution is a mixture of nitric acid, hydrochloric acid and hydrofluoric acid, and digesting the mixed solution to obtain a lithium aluminum titanium phosphate digestion solution;

[0008] S2: diluting the lithium aluminum titanium phosphate digestion solution obtained in step S1 to obtain a lithium aluminum titanium phosphate stock solution, i.e., diluent I, and then taking a portion of the diluent I and diluting it again to obtain diluent II, which is used to detect the content of the main elements of lithium, aluminum, titanium and phosphorus in the lithium aluminum titanium phosphate, and the remaining diluent I is used to detect the content of impurity elements in the lithium aluminum titanium phosphate;

[0009] S3: Prepare standard solutions of the main elements of lithium, aluminum, titanium and phosphorus and standard solutions of impurity elements respectively, and then detect the main element content of the diluted solution II and the impurity element content of the diluted solution I by ICP-OES, so as to complete the detection of the element content of the lithium aluminum titanium phosphate solid electrolyte.

[0010] Compared with the prior art, the present application discloses a method for detecting the element content of a lithium titanium aluminum phosphate solid electrolyte, which has the following advantages: In view of the deficiencies in the prior art, the present application develops a method for processing and detecting the element content of a lithium titanium aluminum phosphate solid electrolyte, wherein the lithium titanium aluminum phosphate can be completely dissolved into a solution detectable by ICP-OES by preparing a mixed acid and digesting it using conventional methods, thereby effectively solving the problem of quantitative analysis of the chemical composition of lithium titanium aluminum phosphate, and the process method is simple and highly accurate, providing effective and necessary technical support for the development and application of solid electrolytes.

[0011] In a possible implementation, in step S1, the chemical formula of the lithium aluminum titanium phosphate is Li 1+ x Al x Ti 2-x (PO4)3, wherein 0<x<2, that is, x can take any value between 0 and 2, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9.

[0012] In a possible implementation, in step S1, in the mixed acid solution, the concentration of nitric acid is 35% to 75%, the concentration of hydrochloric acid is 25% to 40%, and the concentration of hydrofluoric acid is 35% to 50%; in step S1, the volume ratio of nitric acid, hydrochloric acid and hydrofluoric acid is (1 to 18):(4 to 18):(1 to 8).

[0013] In a possible implementation, in step S1, the mixing mass volume ratio of the lithium aluminum titanium phosphate solid electrolyte powder and the mixed acid solution is (0.1000-0.2500 g): (6.0-28.0 ml).

[0014] In the above possible implementation manner of the present invention, by further optimizing the concentration and volume ratio of the mixed acid solution, as well as the mixed mass volume ratio of the lithium titanium aluminum phosphate solid electrolyte powder and the mixed acid solution, by preparing a mixed acid solution of a specific ratio and digesting it using conventional methods, the lithium titanium aluminum phosphate can be completely dissolved into a solution that can be detected in an inductively coupled plasma emission spectrometer, thereby effectively solving the problem of quantitative analysis of the chemical composition of lithium titanium aluminum phosphate and further improving the detection effect.

[0015] In addition, it was found during the preparation process that if the mixed mass volume ratio in the mixed acid is too high, the lithium aluminum titanium phosphate cannot be completely digested into a clear and transparent solution. If the mixed mass volume ratio is too low, the dilution effect will be affected, which will eventually affect the determination of the content. Therefore, only the detection of the lithium aluminum titanium phosphate after digestion can be prepared according to the mass volume ratio of the above-mentioned specific ratio to achieve good results. The applicant also found that only the mixed acid prepared according to the above-mentioned ratio range can be digested to obtain a clear and transparent solution, otherwise it is difficult to completely digest it, and the final result is a solid-liquid mixture, which cannot be detected by ICP-OES. Moreover, according to the above-mentioned ratio of the two simple acids, such as hydrochloric acid and nitric acid, nitric acid and hydrofluoric acid, hydrochloric acid and hydrofluoric acid, no matter how the ratio is, the lithium aluminum titanium phosphate cannot be completely digested, and the solid-liquid mixture is obtained without exception, which obviously cannot achieve the purpose of ICP-OES detection. Therefore, only by mixing the acids in the above-mentioned three ratios, using a specific ratio of mixed acid and a mixed mass volume ratio, can a clear and transparent solution of lithium aluminum titanium phosphate be digested, so that its content can be accurately and quantitatively detected by ICP-OES.

[0016] For sulfuric acid solution, it is found in the process of preparation that for the mixed acid of sulfuric acid, hydrochloric acid and hydrofluoric acid, no matter how the ratio is adjusted, lithium aluminum titanium phosphate cannot be completely digested to obtain a clear and transparent solution, and thus it is impossible to use ICP-OES to quantitatively detect its content. In addition, the atomization efficiency of sulfuric acid solution is low, and it is difficult to rinse, and it is generally not used for ICP-OES detection, and sulfate radicals can produce precipitates with some cations, which can cause interference after digestion, thereby affecting the detection effect. Therefore, whether from the perspective of digestion effect or detection effect, sulfuric acid solution is not conducive to being used to digest lithium aluminum titanium phosphate and detect its content.

[0017] In a possible embodiment, in step S1, the digestion treatment includes: pouring the mixed solution into a digestion tank and sealing it, placing it on an electric heating plate or an electric blast drying oven for low-temperature heating until the sample is completely dissolved into a clear state to obtain a lithium aluminum titanium phosphate digestion solution, wherein the low-temperature heating temperature is 120 to 180°C and the heating time is 1 to 8 hours.

[0018] In a possible implementation manner, in the step S2, the dilution factor is 20-50 times.

[0019] In a possible implementation, in step S3, the steps of preparing standard solutions of the main elements of lithium, aluminum, titanium and phosphorus respectively include: preparing Li / Al 0, 1, 2, 5 mg / L mixed standard solutions and Ti / P 0, 10, 20, 50 mg / L mixed standard solutions respectively; the steps of preparing standard solutions of impurity elements include: preparing impurity elements 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solutions.

[0020] In a possible embodiment, in step S3, the detection method is: detecting the main elements and impurity elements of lithium aluminum titanium phosphate by ICP-OES, testing the lithium content at the characteristic line of 670.784nm, the aluminum content at the characteristic line of 396.153nm, the titanium content at the characteristic line of 334.941nm, and the phosphorus content at the characteristic line of 213.618nm.

[0021] In the above possible implementation manners of the present invention, there is no particular limitation on the operating parameters, instruments or containers involved in the ICP-OES test, and they may be parameters, instruments or containers conventionally used in the art.

[0022] The present application discloses a method for detecting the element content of lithium titanium aluminum phosphate solid electrolyte, the principle of which is that if ICP-OES is to be used to quantitatively detect the substance to be detected, the substance to be detected needs to be completely dissolved into a solution that can be detected by ICP-OES. For lithium titanium aluminum phosphate solid electrolyte, if ICP-OES is to be used to quantitatively determine the content of its components, the lithium titanium aluminum phosphate needs to be completely dissolved into a solution state. Lithium titanium aluminum phosphate is a typical NASICON-type polyanion compound, and its structure has two TiO6 octahedra and three PO4 tetrahedrons connected at the same corner to form a basic structural unit called a "lantern". The rigid crystal skeleton of lithium titanium aluminum phosphate is composed of multiple such "lanterns", and its structure is extremely stable and difficult to destroy. Therefore, it is extremely difficult to completely dissolve lithium titanium aluminum phosphate into a solution state. If lithium titanium aluminum phosphate is to be completely dissolved into a solution state, it is first necessary to consider destroying its rigid valuation structure. The mixed acid digestion scheme provided by the present invention can attack the TiO6 octahedral structure and PO4 tetrahedral structure of lithium titanium aluminum phosphate by preparing a mixed acid solution of a specific ratio, thereby causing the collapse of its rigid skeleton structure, and then it can be completely dissolved into a solution state. Its deeper mechanism of action needs further study.

[0023] The beneficial effect of the present invention is that a method for detecting the element content of lithium titanium aluminum phosphate solid electrolyte is provided, and the lithium titanium aluminum phosphate is digested to a solution state by preparing a mixed acid solution of a specific ratio, so that the content of its components can be accurately and quantitatively detected by ICP-OES, thereby solving the difficult problem of detecting the element content of lithium titanium aluminum phosphate solid electrolyte, and having great guiding significance for its application in the field of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are part of this application and are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute improper limitations on the present invention. Obviously, the accompanying drawings described below are only some embodiments, and a person of ordinary skill in the art can obtain other accompanying drawings based on these accompanying drawings without paying any creative work.

[0025] Figure 1 The present invention is a process flow chart of a method for treating a lithium aluminum titanium phosphate solid electrolyte and detecting the element content.

[0026] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0027] The following examples are for a better understanding of the present invention, are not limited to the best mode of implementation, and are not intended to limit the content and scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts, falls within the protection scope of the present invention. Obviously, those skilled in the art can easily recognize that some of the features can be omitted in different situations, or can be replaced by other materials and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.

[0028] The process equipment or devices not specifically indicated in the following examples all adopt conventional equipment or devices in the art. In addition, the protection scope of the present invention is not limited to the following specific specific embodiments, and the one or more method steps mentioned in the present invention do not exclude that there may be other method steps before and after the combination step or other method steps may be inserted between these explicitly mentioned steps, unless otherwise specified. In addition, the characteristics, operations or features described in the specification can be combined in any appropriate manner to form various embodiments. At the same time, the steps or actions in the method description can also be sequentially exchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the accompanying drawings are only for the purpose of clearly describing a certain embodiment, and do not mean that they are necessary sequences, unless otherwise specified that a certain sequence must be followed. If the specific experimental steps or conditions are not indicated in the embodiments, the operations or conditions of the conventional experimental steps described in the literature in the art can be carried out. If the manufacturer of the reagents or instruments used is not indicated, they can be obtained through commercial channels.

[0029] The present invention provides a method for detecting the element content after treating lithium aluminum titanium phosphate solid electrolyte, such as Figure 1 As shown, Figure 1 For the process flow chart of the present invention, the following is combined with Figure 1 The present invention is further described.

[0030] The present invention provides a method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte, comprising the following steps:

[0031] S1: mixing lithium aluminum titanium phosphate solid electrolyte powder to be tested with a mixed acid solution to obtain a mixed solution, wherein the mixed acid solution is a mixture of nitric acid, hydrochloric acid and hydrofluoric acid, and digesting the mixed solution to obtain a lithium aluminum titanium phosphate digestion solution;

[0032] S2: diluting the lithium aluminum titanium phosphate digestion solution obtained in step S1 to obtain a lithium aluminum titanium phosphate stock solution, i.e., diluent I, and then taking a portion of the diluent I and diluting it again to obtain diluent II, which is used to detect the content of the main elements of lithium, aluminum, titanium and phosphorus in the lithium aluminum titanium phosphate, and the remaining diluent I is used to detect the content of impurity elements in the lithium aluminum titanium phosphate;

[0033] S3: Prepare standard solutions of the main elements of lithium, aluminum, titanium and phosphorus and standard solutions of impurity elements respectively, and then detect the main element content of the diluted solution II and the impurity element content of the diluted solution I by ICP-OES, so as to complete the detection of the element content of the lithium aluminum titanium phosphate solid electrolyte.

[0034] As a preferred solution, the chemical formula of the lithium aluminum titanium phosphate is Li 1+x Al x Ti 2-x (PO4)3, wherein 0<x<2, that is, x can take any value between 0 and 2, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9.

[0035] As a preferred scheme, in the mixed acid solution, the concentration of nitric acid is 35% to 75%, the concentration of hydrochloric acid is 25% to 40%, and the concentration of hydrofluoric acid is 35% to 50%; in the step S1, the volume ratio of the nitric acid, hydrochloric acid and hydrofluoric acid is (1 to 18):(4 to 18):(1 to 8).

[0036] As a preferred solution, in step S1, the mixing mass volume ratio of the lithium aluminum titanium phosphate solid electrolyte powder and the mixed acid solution is (0.1000-0.2500 g): (6.0-28.0 ml).

[0037] As a preferred scheme, in the step S1, the digestion treatment includes: pouring the mixed solution into a digestion tank and sealing it, placing it on an electric heating plate or an electric blast drying oven for low-temperature heating until the sample is completely dissolved into a clear state to obtain a lithium aluminum titanium phosphate digestion solution, the low-temperature heating temperature is 120-180°C, and the heating time is 1-8h.

[0038] As a preferred solution, in step S2, the dilution factor is 20-50 times.

[0039] As a preferred scheme, in the step S3, the steps of preparing standard solutions of the main elements of lithium, aluminum, titanium and phosphorus respectively include: preparing Li / Al 0, 1, 2, 5 mg / L mixed standard solution and Ti / P 0, 10, 20, 50 mg / L mixed standard solution respectively; the step of preparing the standard solution of the impurity element includes: preparing 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solution of the impurity element.

[0040] As a preferred scheme, in the step S3, the detection method is: the main elements and impurity elements of lithium aluminum titanium phosphate are detected by ICP-OES, and the lithium content is tested at the characteristic line of 670.784nm, the aluminum content is tested at the characteristic line of 396.153nm, the titanium content is tested at the characteristic line of 334.941nm, and the phosphorus content is tested at the characteristic line of 213.618nm; in the present invention, there is no special limitation on the operating parameters, instruments or containers involved in the ICP-OES test, and they can be the parameters, instruments or containers conventionally used in the art.

[0041] In order to further understand the present invention, the treatment of the lithium aluminum titanium phosphate solid electrolyte and the detection method of the element content provided by the present invention are described in detail below in conjunction with specific embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0042] Example 1

[0043] This embodiment provides a method for detecting the element content after treating lithium aluminum titanium phosphate solid electrolyte, and the preparation method comprises the following steps:

[0044] S1. Accurately weigh about 0.1000g of lithium aluminum titanium phosphate solid electrolyte powder (Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (x = 0.3)) in a polytetrafluoroethylene digestion bottle, add 10.0 ml of mixed acid (mixed in a volume ratio of 4:12:1 of 50% nitric acid, 35% hydrochloric acid and 40% hydrofluoric acid), seal it and place it in an electric blast drying oven at 150°C for 6 hours until the sample is completely dissolved to obtain a lithium aluminum titanium phosphate digestion solution;

[0045] S2, cooling the lithium aluminum titanium phosphate solution obtained in step S1 and transferring it to a 50 ml volumetric flask to obtain diluent I, and preparing a sample blank at the same time. This solution (diluent I) is used to test the impurity elements, and then a portion of the lithium aluminum titanium phosphate stock solution (diluent I) is diluted 50 times to obtain (diluent II) for testing the major elements (lithium, aluminum, titanium and phosphorus);

[0046] S3. Prepare Li / Al 0, 1, 2, 5 mg / L mixed standard solution, Ti / P 0, 10, 20, 50 mg / L mixed standard solution, and impurity element 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solution, and then use ICP-OES to detect the main element content and impurity element content of lithium aluminum titanium phosphate. The lithium content is tested at the characteristic line of 670.784 nm, the aluminum content is tested at the characteristic line of 396.153 nm, the titanium content is tested at the characteristic line of 334.941 nm, and the phosphorus content is tested at the characteristic line of 213.618 nm. There is no special limitation on the operating parameters, instruments or containers involved in the ICP-OES test, and they can be the parameters, instruments or containers conventionally used in the art;

[0047] Example 1 was tested three times with the same specifications and experimental conditions, and the three groups tested by Example 1 were named 1#, 2#, and 3#.

[0048] Example 2

[0049] This embodiment provides a method for detecting the element content after treating lithium aluminum titanium phosphate solid electrolyte, and the preparation method comprises the following steps:

[0050] S1. Accurately weigh about 0.2500 g of lithium aluminum titanium phosphate solid electrolyte powder (Li 1.3 Al 0.3 Ti 1.7 (PO4)3(x=0.3)) was placed in a polytetrafluoroethylene digestion bottle, 10.0 ml of mixed acid (mixed in a volume ratio of 12:4:1 of 35% nitric acid, 30% hydrochloric acid and 35% hydrofluoric acid) was added, and the mixture was sealed and placed in an electric blast drying oven at 180°C for 4 h until the sample was completely dissolved to obtain a lithium aluminum titanium phosphate digestion solution;

[0051] S2, cooling the lithium aluminum titanium phosphate solution obtained in step S1 and transferring it to a 50 ml volumetric flask to obtain diluent I, and preparing a sample blank at the same time. This solution (dilution I) is used to test the impurity elements, and then a portion of the lithium aluminum titanium phosphate stock solution (dilution I) is diluted 20 times to obtain (dilution II) for testing the major elements (lithium, aluminum, titanium and phosphorus);

[0052] S3. Prepare Li / Al 0, 1, 2, 5 mg / L mixed standard solution, Ti / P 0, 10, 20, 50 mg / L mixed standard solution, impurity element 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solution, and then detect the main element content and impurity element content of lithium aluminum titanium phosphate by ICP-OES. The lithium content is tested at the characteristic line of 670.784 nm, the aluminum content is tested at the characteristic line of 396.153 nm, the titanium content is tested at the characteristic line of 334.941 nm, and the phosphorus content is tested at the characteristic line of 213.618 nm. There is no special limitation on the operating parameters, instruments or containers involved in the ICP-OES test, and they can be the parameters, instruments or containers conventionally used in the art.

[0053] Example 3

[0054] This embodiment provides a method for detecting the element content after treating lithium aluminum titanium phosphate solid electrolyte, and the preparation method comprises the following steps:

[0055] S1. Accurately weigh about 0.1000g of lithium aluminum titanium phosphate solid electrolyte powder (Li 1.5 Al 0.5 Ti 1.5 (PO4)3(x=0.5)) in a polytetrafluoroethylene digestion bottle, add 10.0ml of mixed acid (mixed in a volume ratio of 4:12:1 of 50% nitric acid, 35% hydrochloric acid and 40% hydrofluoric acid), seal it and heat it on an electric heating plate at 180℃ for 4h until the sample is completely dissolved to obtain a lithium aluminum titanium phosphate digestion solution;

[0056] S2, cooling the lithium aluminum titanium phosphate solution obtained in step S1 and transferring it to a 50 ml volumetric flask to obtain diluent I, and preparing a sample blank at the same time. This solution (diluent I) is used to test the impurity elements, and then a portion of the lithium aluminum titanium phosphate stock solution (diluent I) is diluted 50 times to obtain (diluent II) for testing the major elements (lithium, aluminum, titanium and phosphorus);

[0057] S3. Prepare Li / Al 0, 1, 2, 5 mg / L mixed standard solution, Ti / P 0, 10, 20, 50 mg / L mixed standard solution, impurity element 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solution, and then detect the main element content and impurity element content of lithium aluminum titanium phosphate by ICP-OES. The lithium content is tested at the characteristic line of 670.784 nm, the aluminum content is tested at the characteristic line of 396.153 nm, the titanium content is tested at the characteristic line of 334.941 nm, and the phosphorus content is tested at the characteristic line of 213.618 nm. There is no special limitation on the operating parameters, instruments or containers involved in the ICP-OES test, and they can be the parameters, instruments or containers conventionally used in the art.

[0058] Example 4

[0059] This embodiment provides a method for detecting the element content after treating lithium aluminum titanium phosphate solid electrolyte, and the preparation method comprises the following steps:

[0060] S1. Accurately weigh about 0.2000g of lithium aluminum titanium phosphate solid electrolyte powder (Li 1.7 Al 0.7 Ti 1.3 (PO4)3 (x = 0.7)) in a polytetrafluoroethylene digestion bottle, add 10.0 ml of mixed acid (mixed in a volume ratio of 65% nitric acid, 35% hydrochloric acid and 40% hydrofluoric acid of 1:12:4), seal it and place it in an electric blast drying oven at 120°C for 8 hours until the sample is completely dissolved to obtain a lithium aluminum titanium phosphate digestion solution;

[0061] S2, cooling the lithium aluminum titanium phosphate solution obtained in step S1 and transferring it to a 50 ml volumetric flask to obtain diluent I, and preparing a sample blank at the same time. This solution (diluent I) is used to test the impurity elements, and then a portion of the lithium aluminum titanium phosphate stock solution (diluent I) is diluted 40 times to obtain (diluent II) for testing the major elements (lithium, aluminum, titanium and phosphorus);

[0062] S3. Prepare Li / Al 0, 1, 2, 5 mg / L mixed standard solution, Ti / P 0, 10, 20, 50 mg / L mixed standard solution, impurity element 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solution, and then detect the main element content and impurity element content of lithium aluminum titanium phosphate by ICP-OES. The lithium content is tested at the characteristic line of 670.784 nm, the aluminum content is tested at the characteristic line of 396.153 nm, the titanium content is tested at the characteristic line of 334.941 nm, and the phosphorus content is tested at the characteristic line of 213.618 nm. There is no special limitation on the operating parameters, instruments or containers involved in the ICP-OES test, and they can be the parameters, instruments or containers conventionally used in the art.

[0063] The following provides the results of the detection methods of the above-mentioned embodiments 1-4, so as to further illustrate the technical effects of the present invention:

[0064] As shown in Table 1 and Table 2, Table 1 is the test results of the main element content of lithium titanium aluminum phosphate in Examples 1 to 4, wherein Table 1 also includes the respective test results and the average results of the three groups 1#, 2#, and 3# in Example 1; Table 2 is the test results of the impurity element content of lithium titanium aluminum phosphate, wherein the results of Examples 1-4 are all average values ​​obtained after multiple tests.

[0065] Table 1 Main element content of lithium aluminum titanium phosphate

[0066]

[0067] It should be noted that the results of Examples 2-4 in the above Table 1 are the average values ​​of the results of three tests. At the same time, the present invention exemplarily provides three test results of Example 1 to confirm that the method provided by the present invention has good reproducibility.

[0068] In the present invention, the theoretical content refers to a solid electrolyte with a certain molecular formula, such as Li 1+x Al x Ti 2-x The theoretical content of lithium, aluminum, titanium and phosphorus in (PO4)3 is calculated by the following formula:

[0069] Li theoretical content = M Li ×(1+x) / (M Li ×(1+x)+M Al ×x+M Ti ×(2-x)+M P ×3+M O ×12)×100%;

[0070] Al theoretical content = M Al ×x / (M Li ×(1+x)+M Al ×x+M Ti ×(2-x)+M P ×3+M O ×12)×100%;

[0071] Theoretical Ti content = M Ti ×(2-x) / (M Li ×(1+x)+M Al ×x+M Ti ×(2-x)+M P ×3+M O ×12)×100%;

[0072] P theoretical content = M P ×3 / (M Li ×(1+x)+M Al ×x+M Ti ×(2-x)+M P ×3+M O ×12)×100%;

[0073] Table 2 Impurity element content of lithium aluminum titanium phosphate

[0074] Example 1 Example 2 Example 3 Example 4 Fe / ppm 1.07 0.96 1.11 0.87 Co / ppm 0.79 0.93 1.01 0.87 Ni / ppm 1.57 1.68 1.71 1.69 Zn / ppm 1.21 1.09 1.14 1.38 Cu / ppm 0.69 0.81 0.65 0.94 Mn / ppm 1.63 1.57 1.83 1.69 Na / ppm 57.83 68.42 71.12 64.28 K / ppm 7.89 6.85 9.26 8.13 Mg / ppm 19.23 21.15 22.98 20.87

[0075] The results of Examples 1-4 in Table 2 above are the average values ​​of the results of three tests to verify that the method provided by the present invention has good reproducibility.

[0076] It can be seen from the above results that by adopting the method provided by the present invention, the lithium titanium aluminum phosphate solid electrolyte is mixed with a mixed acid in a specific proportion and then digested in a conventional manner, so that a solid electrolyte test solution for ICP testing can be obtained, and then the content of the main elements of lithium, aluminum, titanium, and phosphorus and the content of impurity elements in the solid electrolyte can be tested. The method is simple and reliable, with good reproducibility, and effectively solves the problem of quantitative analysis of the chemical composition of lithium titanium aluminum phosphate. The process method is simple and accurate, and provides effective and necessary technical support for the development and application of solid electrolytes.

[0077] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

[0079] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and to form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte, characterized in that: The following steps are involved: S1: mixing lithium aluminum titanium phosphate solid electrolyte powder to be tested with a mixed acid solution to obtain a mixed solution, wherein the mixed acid solution is a mixture of nitric acid, hydrochloric acid and hydrofluoric acid, and digesting the mixed solution to obtain a lithium aluminum titanium phosphate digestion solution; S2: diluting the lithium aluminum titanium phosphate digestion solution obtained in step S1 to obtain a lithium aluminum titanium phosphate stock solution, i.e., diluent I, and then taking a portion of the diluent I and diluting it again to obtain diluent II, which is used to detect the content of the main elements of lithium, aluminum, titanium and phosphorus in the lithium aluminum titanium phosphate, and the remaining diluent I is used to detect the content of impurity elements in the lithium aluminum titanium phosphate; S3: Prepare standard solutions of the main elements of lithium, aluminum, titanium and phosphorus and standard solutions of impurity elements respectively, and then detect the main element content of the dilution solution II and the impurity element content of the dilution solution I by ICP-OES, i.e., inductively coupled plasma emission spectrometry, to complete the detection of the element content of lithium aluminum titanium phosphate solid electrolyte.

2. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S1, the chemical formula of lithium aluminum titanium phosphate is Li 1+x Al x Ti 2-x (PO4)3, where 0<x<2.

3. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In the step S1, in the mixed acid solution, the concentration of nitric acid is 35-75%, the concentration of hydrochloric acid is 25-40%, and the concentration of hydrofluoric acid is 35-50%; in the step S1, the volume ratio of nitric acid, hydrochloric acid and hydrofluoric acid is (1-18):(4-18):(1-8).

4. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 3, characterized in that: In the step S1, the mixing mass volume ratio of the lithium aluminum titanium phosphate solid electrolyte powder and the mixed acid solution is (0.1000-0.2500 g): (6.0-28.0 ml).

5. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In the step S1, the digestion treatment includes: pouring the mixed solution into a digestion tank and sealing it, placing it on an electric heating plate or an electric blast drying oven for low-temperature heating until the sample is completely dissolved into a clear state to obtain a lithium aluminum titanium phosphate digestion solution, wherein the low-temperature heating temperature is 120 to 180° C. and the heating time is 1 to 8 hours.

6. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In the step S2, the dilution factor is 20-50 times.

7. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S3, the steps of preparing standard solutions of the main elements of lithium, aluminum, titanium and phosphorus respectively include: preparing Li / Al 0, 1, 2, 5 mg / L mixed standard solutions and Ti / P 0, 10, 20, 50 mg / L mixed standard solutions respectively; the step of preparing standard solutions of impurity elements includes: preparing impurity elements 0, 0.05, 0.10, 0.50, 1.0, 5.0 mg / L mixed standard solutions.

8. The method for detecting the element content of lithium aluminum titanium phosphate solid electrolyte according to claim 7, characterized in that: In step S3, the detection method is: the main elements and impurity elements of lithium aluminum titanium phosphate are detected by ICP-OES, and the lithium content is tested at the characteristic line of 670.784nm, the aluminum content is tested at the characteristic line of 396.153nm, the titanium content is tested at the characteristic line of 334.941nm, and the phosphorus content is tested at the characteristic line of 213.618nm.

Citation Information

Cited By

  • Method for detecting chemical components in Li2TiO3 microspheres

    CN121656229A